Being ACTIVE in Legal Translation and Interpreting: Researching and Acting on the Spanish Field - Monzó, Esther (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractTranslation is not a profession. That was the conclusion of a study carried out by the author among Spanish legal translators. However, there are strategies which may be used by researchers in order to promote the social, cultural and economic interests of these professionals, mainly by applying Lewin’s methodology of action-research. This paper presents a research project currently being carried out by the ACTIVE team, which seeks to describe and explain a small part of the translation and interpreting field — that devoted to the intersystemic communication of law. By exploring and promoting the interests and strategies of certified translators and interpreters in the Spanish context we aim to improve their professional practice conditions.